Casirivimab/imdevimab + remdesivir in hospitalized patients with severe Covid-19: A single centre experience. Issue 2 (February 2023) - Moriello, Nicola Schiano; Buonomo, Antonio Riccardo; Scotto, Riccardo; Pinchera, Biagio; Sarno, Marina; Fusco, Ludovica; Viceconte, Giulio; Iuliano, Antonio; Zappulo, Emanuela; Foggia, Maria; Villari, Riccardo; Gentile, Ivan
Abstract: Since 2020, COVID-19 pandemic has spread worldwide causing a huge number of cases and casualties. Among direct anti SARS-CoV-2 agents available for the treatment of COVID-19, only remdesivir and casirivimab/imdevimab have been approved for severe disease. As they act at different levels in blocking viral replication, it is theoretically possible to combine them. In this case series we describe tolerability, safety and effectiveness in a small group of 14 patients of the combination of casirivimab/imdevimab monoclonal antibodies with the polymerase inhibitor remdesivir for the treatment of severe COVID-19. We conducted a retrospective study among consecutive patients admitted to the Infectious Disease ward of the University of Naples (Italy) Hospital for COVID-19 that received the combination of casirivimab/imdevimab and remdesivir for the treatment of severe COVID-19 from the August 1, 2021 to the November 30, 2021. During the study period, 78 patients were admitted for severe COVID-19. Fourteen patients (18%) received the combination casirivimab/imdevimab and remdesivir. They were five males and nine females with a median age of 54 years. Eight patients had significant comorbidities; three patients were in the immediate post-partum period. No adverse drug reaction was observed. All patients except one improved clinical condition and respiratory parameters within seven days following the therapy. All patients were discharged in good conditions.